2018
DOI: 10.16899/gopctd.387725
|View full text |Cite
|
Sign up to set email alerts
|

Ig-A vasküliti (Henoch-Schönlein purpurası) Tanısı Alan Çocuklarda Trombosit İndekslerinin Klinik Önemi

Abstract: Çocuk acil kliniğinde Ig-A vasküliti (Henoch-Schönlein purpurası) tanısı alan çocuklarda trombosit indekslerinin klinik önemi Clinical importance of platelet indexes in children diagnosed with Ig-A vasculitis (Henoch-Schönlein Purpura) in children's emergency clinic Amaç: Ig-A vasküliti, çoğunlukla kendi kendini sınırlayan, cilt, eklem, gastrointestinal sistem ve böbrek tutulumu ile karakterize, çocukluk çağı sistemik vaskülitinin en yaygın şeklidir. Biz bu çalışmada, Ig-A vaskülitli hastaların demografik özel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…IgAV/HSP is most common between 3-15 years of age and peaks between 5-7 years of age [9][10][11]. In studies from Turkey, the mean age of IgAV/HSP has been reported to be between 7 and 9 years [3,6,[12][13][14]. In our study, the age of onset was 7.5±3.0 years, and males and females were equally affected.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…IgAV/HSP is most common between 3-15 years of age and peaks between 5-7 years of age [9][10][11]. In studies from Turkey, the mean age of IgAV/HSP has been reported to be between 7 and 9 years [3,6,[12][13][14]. In our study, the age of onset was 7.5±3.0 years, and males and females were equally affected.…”
Section: Discussionsupporting
confidence: 55%
“…In our study, the age of onset was 7.5±3.0 years, and males and females were equally affected. In the literature, besides the studies reporting gender equality, there are also studies showing male, or female dominance [3,6,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations